Persistence of dysfunctional immune response 12 months after SARS-CoV-2 infection and their relationship with pulmonary sequelae and long COVID - Tamara Cruz; Núria Albacar; Estibaliz Ruiz; Gema M. Lledo; Lídia Perea; Alba Puebla; Alejandro Torvisco; Núria Mendoza; Pau Marrades; Jacobo Sellares; Alvar Agustí; Odette Viñas; et al. (Respiratory Research)
Abstract Introduction Most patients recover fully after an acute infection by SARS-CoV-2. Some, however, may develop pulmonary sequelae (PS) and/or long COVID (LC). However, whether these two clinical conditions have similar or different pathogenic mechanisms is unknown. Methods The levels of autoantibodies and 184 inflammatory and organ damage associated proteins in plasma were determined (by immunofluorescence and Olink panels, respectively) 1 year after an acute infection by SARS-CoV-2 in 51 patients with PS (DLCO < 80% ref), 31 patients with LC and 31 patients fully recovered (Rec). PS was defined by the presence of reduced carbon monoxide diffusing capacity (DLCO) lower than 80% ref. LC was defined by the presence of chronic symptoms in the absence of an alternative diagnosis. Results We found that patients with PS or LC both showed increased levels than Rec of anti-microbial, immune cell activation and recruitment related proteins. Patients with PS showed higher levels of anti-nuclear autoantibodies, whereas LC patients had increased levels of organ-damage associated proteins. In patients with PS most of the elevated proteins correlate with the impairment of lung function (DLCO). Finally, in PS we additionally performed the determinations at an earlier time point (6 months) and showed that the expression of CCL20 and IFN-ɣ was already higher at 6 months, while CCL3 and CCL19 increase from 6 to 12 months, suggesting a pathogenic role in PS persistence. Conclusions Patients with PS or LC have abnormal but different persistent circulatory immune and organ damage biomarkers, suggesting different underlying biology of both post-COVID conditions.